1999
DOI: 10.1080/07315179908241296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field on domain formation in relaxor based Pb(Zn1/3Nb2/3)O3- PbTiO3single crystals

Abstract: Domain switching has been observed in 0. 9PZN -0. 1PT single crystals under the influence of electric field. The crystal being near the morphotropic phase boundary contains two phases -rhombohedra1 and tetragonbal. The electric field was applied along two principal directions [OOl] and [lli]. Their formation as the temperature is reduced with the electric field is discussed here. For electric field along [OOl]. it was found that a single domain could be induced in tetragonal phase. When the electric field was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…On the other hand, the symmetry lowering from the tetragonal or rhombohedral phase in the MPB region (PZN-9%PT) was reported in terms of the observation of the indicatrix rotation [5]. The domain-wall structure strongly depends on the mechanical and electrical conditions [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, the symmetry lowering from the tetragonal or rhombohedral phase in the MPB region (PZN-9%PT) was reported in terms of the observation of the indicatrix rotation [5]. The domain-wall structure strongly depends on the mechanical and electrical conditions [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…7) The domain-wall structure strongly depends on the mechanical and electrical conditions. 8,9) In a previous paper, 10) we reported, on the basis of the observation obtained using a polarizing microscope, that the sharp phase transition between the tetragonal and rhombohedral phases in the PZN-PT crystal can be observed in the small region of 50 mm order even without the poling process. We also found that the principal axis of the indicatrix slightly rotates in the MPB region, implying the appearance of a lower symmetry phase such as a monoclinic phase.…”
Section: Introductionmentioning
confidence: 95%
“…1 PT is also the end member of PbZrO 3 -PbTiO 3 (PZT), Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT) and Pb(Zn 1/3 Nb 2/3 )O 3 -PbTiO 3 (PZN-PT), which have been widely applied in modern piezoelectric devices. [2][3][4][5] With the miniaturization of these devices, PT-based nanostructures have been intensively investigated, [6][7][8][9] which are desirable objects for the understanding of ferroelectricity and piezoelectricicty at the nanoscale. In the past few years, various single-crystal PT nanostructures, including nanodots, 10 nanofibers 11 and nanoplates, 12 were synthesized successfully.…”
Section: Introductionmentioning
confidence: 99%